Analysis of Education Quality Through Zonational Admission, Review of Academic and Non-Academic Aspects - Mudzakir, Asep; Zulaikha, Siti; Suryadi (Jurnal Inspirasi Pendidikan, 2024)
This study aims to analyze the quality of education at SMA Negeri 1 Serang City through the implementation of the zoning-based New Student Admission (PPDB) policy, focusing on both academic and non-academic aspects. The zoning-based PPDB policy is expected to enhance educational equity by providing fairer opportunities for students to access nearby schools. This research employs a qualitative method with a case study approach. Data were collected through in-depth interviews, observations, and relevant document analysis. The research informants included teachers, students, and parents at SMA Negeri 1 Serang City. The findings indicate that the zoning-based PPDB policy has a positive impact on the quality of education in non-academic aspects, particularly in terms of student diversity and the improvement of social skills. However, from an academic perspective, several challenges were identified, such as significant disparities in students' competency levels, which affect the teaching and learning process in the classroom. Additionally, this policy presents new challenges for teachers in adapting instructional methods to meet the diverse needs of students. Although improvements in non-academic aspects have been observed, overall educational quality still requires adequate policy support and resources to address academic disparities. The findings of this study contribute to the understanding of the impact of the zoning-based PPDB policy on education quality and provide recommendations for improving more comprehensive educational services.